Co-depositing bio-inspired tannic acid-aminopropyltriethoxysilane coating onto carbon fiber for excellent interfacial adhesion of epoxy composites. (1st March 2021) - Zhang, Mengjie; Cheng, Chunxia; Guo, Chunqi; Jin, Lin; Liu, Liu; Li, Ming; Shang, Lei; Liu, Yu; Ao, Yuhui
Abstract: The mechanical properties of carbon fiber reinforced polymer (CFRP) are seriously affected by the poor interfacial adhesion between carbon fiber (CF) and resin matrix. Therefore, it was necessary to modify the surface of CF, but this process also confronted the problems of environmental pollution and harsh conditions. Herein, tannic acid (TA) and aminopropyltriethoxysilane (APTES) were co-depositing onto the surface of CF in aqueous solution by a mild and eco-friendly method to improve interfacial properties. Due to the unique adhesion properties of TA and its oxidation products can react with APTES, the products can be uniformly coated on the inert surface of CF. At the same time, the coating introduced a number of amino groups into the surface of the CF and promoted the chemical interaction between CF and epoxy matrix. The IFSS, transverse fiber bundle tensile (TFBT) and ILSS of composites after co-deposition were improved, corresponding to 71.3%, 58.5% and 59.9%, respectively. Hence, this work provided a new idea for the green and sustainable development of modified CF. Graphical abstract: Image 1